2011
DOI: 10.1021/ie100674s
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)/Ammonium Polyphosphate Systems Improved Simultaneously Both Fire Retardancy and Mechanical Properties by Montmorillonite

Abstract: The effect of montmorillonite (MMT) used to improve the fire retardancy of poly(vinyl alcohol) (PVA)/ammonium polyphosphate (APP) was studied. The limiting oxygen index (LOI), vertical burning test (UL-94), cone calorimeter, thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) were used to evaluate the effect of the presence of MMT. Compared to that for the PVA/APP composite, the LOI of PVA/APP/MMT composite was increased from 27.9 to 30.8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…However, these peaks still exist at 400°C and almost disappear at 500°C for RPUF/15EG/5AHP. Usually, the absorption peaks of aliphatic CH bond in the range of 2800 to 3000 cm −1 are used to evaluate the thermal oxidation stability of polymer . This is because with the increase of temperature, the polymer molecular chain degrades gradually, causing the intensity of the absorption peaks of CH bond to weaken gradually and the absorption peaks of CH bond almost disappear when the polymer molecular chain degrades completely.…”
Section: Resultsmentioning
confidence: 99%
“…However, these peaks still exist at 400°C and almost disappear at 500°C for RPUF/15EG/5AHP. Usually, the absorption peaks of aliphatic CH bond in the range of 2800 to 3000 cm −1 are used to evaluate the thermal oxidation stability of polymer . This is because with the increase of temperature, the polymer molecular chain degrades gradually, causing the intensity of the absorption peaks of CH bond to weaken gradually and the absorption peaks of CH bond almost disappear when the polymer molecular chain degrades completely.…”
Section: Resultsmentioning
confidence: 99%
“…8b-d, first of all, there are no obviously IFR characteristic peaks, meaning that IFR has been almost decomposed and volatilized before 500 °C. Then, it can be found that the peak at 987 cm -1 can be ascribed to the stretching vibration of P-O-P [4]. The characteristic absorption peaks (~1200 cm -1 and ~1150 cm -1 ) in the 1100-1300 cm -1 range are assigned to the P-O bands belonging to the HAC char, ZrP 2 O 7 .…”
Section: Ftir Spectra Of Char Residuesmentioning
confidence: 93%
“…In recent years, poly(vinyl alcohol) (PVA) has received particular attention in the field of polymer composites due to its excellent chemical resistance, easy processability, biodegradability, and water solubility [1][2][3][4][5]. In this case, PVA can be widely used in proton exchange membranes, packing materials and artificial biomedical devices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…MXene/chitosan nanocoating is conductive to suppressing the release of heat and smoke in TPU via the layer-by-layer (LbL) approach, but there is drawback in the complex manipulation [22]. Moreover, traditional nanomaterials can effectively improve the flame retardant performances of the system, however, there they have defects such as large addition or the need for surface modification of the nanomaterials [23][24][25][26][27]. In this work, with our simple strategy without any chemical modification, the introduction of MXene and APP to PVA leads to a significant decrease in PHRR (55%), THR (33.6%) and PSPR (74%), which are better than majority of results reported in the literature, suggesting the superior flame retardant and smoke suppression performance of the proposed combination.…”
Section: Fire Behaviormentioning
confidence: 99%